The ubiquity of Japanese informality and Okinawan Moai (模合) - Abel Polese (economic sociology. perspectives and conversations, 2022)
One of the first things you'll hear when arriving in Japan, as a scholar of informality, is that while Japanese society may look very formal, with everything strictly controlled and formalized, in fact it is not. Eventually, although the informal practices you're used to observing abroad do not exist here, and may be strictly regulated, precisely where a foreigner would not expect to find informality is where informality will rule. In many respects, it may be said that Japan is like a "negative" of informality: whatever is formal in your country will be informal here, and vice versa.
Keywords: 300